A cross-sectional study to determine prevalence of neonatal dermatoses in a tertiary health care centre of Andhra Pradesh, South India - Deepti Vemu; Shalini Eslavat; Shankar Kunti; Prasad Naik NM; Ritu Gujarati Vishwanath; Sruthi Kamatham (Journal of Krishna Institute of Medical Sciences University)
Background: By definition, the term "neonatal dermatoses" refers to a broad range of cutaneous conditions that develop in the first four weeks of life. Dermatologists and paediatricians must be able to recognize typical events and distinguish them from the more serious cutaneous illnesses that affect newborns. Aim and Objectives: To assess the prevalence of dermatoses in the neonatal period and to find the association with some of the demographic, neonatal and obstetric variables. Material and Methods: This study was a cross sectional study with a sample size of 600 neonates who attended the outpatient department of dermatology in a private medical college in Andhra Pradesh between May 2021 and April 2022. All full-term babies with birth weight > 2.5 kg of both sexes within neonatal period born with normal delivery and caesarean section were included in the study. Results: Out of 600 neonates, 312 (56%) were males, and 502/600 (87.3%) presented with dermatoses. A total of 17 types of dermatoses were diagnosed. The prevalent dermatoses in decreasing order were Mongolian Spots (MS) 196 (32.7%); Erythema Toxicum Neonatorum (ETN) 86 (14.3%); and Physiological Desquamation (PD) 66 (11%). Miniature pubertal signs were commonly observed in newborns of multiparous women (p <0.05) amongst which, genital hyper pigmentation (p = 0.03) was most common (p < 0.01). Naevi and PD were associated with vaginal deliveries (p = 0.03). Conclusion: Dermatosis in neonates was associated with high parity, vaginal delivery, and consanguinity. Most of them were physiological changes. These are to be differentiated and reassurance must be given to the parents who are worried about the children.